The Occupational Safety and Health Scorecard – a business case example for strategic management - Köper, Birgit; Möller, Klaus; Zwetsloot, Gerard (Scandinavian Journal of Work, Environment & Health, 2009)
' ' OBJECTIVE ': 'Human resources and health issues are crucial in terms of corporate competitiveness. However, systematic, continuous and strategically aligned occupational safety and health (OSH) management is scarcely applied in companies. One major reason for this could be the lack of generally accepted and standardised OSH control methods. Our objective was thus to conceptualize a method by which qualitative factors such as human resources and OSH aspects contribute to the performance or value-added layer of an organization. ' ' METHODS ': 'We developed a business case based on the well-known and accepted Balanced Scorecard approach, which we adapted and applied to the management of OSH issues. The concept was implemented in the course of a comprehensive case study at a German automobile manufacturer. We gathered health as well as finance data in order to test which health-related indicators had an impact on financial performance. The demonstration of, and reporting on, how the promotion of workplace health contributes strategically to the organization is crucial for both health and human resource managers. ' ' RESULTS ': 'Based on multivariate regression analyses, our main finding was that the Balanced Scorecard approach is an adequate means to control OSH issues in terms of strategic health management. Our analyses demonstrated that health-related interventions contribute significantly to performance aspects such as quality, productivity, absenteeism, and cost reduction. Therefore, the financial impact of health-related aspects / interventions could be demonstrated by means of the OSH scorecard. ' ' CONCLUSIONS ': 'The availability and quality of health data within the context of overall corporate performance data needs to be improved in order to bridge OSH-related and performance issues of an organization.
Keywords: Balanced Scorecard; business case; business performance; case study; cause and effect chain; constructive research approach; empirical study; human resource management; management control; occupational safety and health; Occupational Safety and Health Scorecard; organizational performance; performance indicator; strategic management